Silymarin and its constituents in cardiac preconditioning - Zholobenko, A; Modriansky, M (Fitoterapia, 2014)
Silymarin, a standardised extract of Silybum marianum (milk thistle), comprises mainly of silybin, with dehydrosilybin (DHSB), quercetin, taxifolin, silychristin and a number of other compounds which are known to possess a range of salutary effects. Indeed, there is evidence for their role in reducing tumour growth, preventing liver toxicity, and protecting a number of organs against ischemic damage. The hepatoprotective effects of silymarin, especially in preventing Amanita and alcohol intoxication induced damage to the liver, are a well established fact. Likewise, there is weighty evidence that silymarin possesses antimicrobial and anticancer activities. Additionally, it has emerged that in animal models, silymarin can protect the heart, brain, liver and kidneys against ischemia reperfusion injury, probably by preconditioning. The mechanisms of preconditioning are, in general, well studied, especially in the heart. On the other hand, the mechanism by which silymarin protects the heart from ischemia remains largely unexplored. This review, therefore, focuses on evaluating existing studies on silymarin induced cardioprotection in the context of the established mechanisms of preconditioning.
Keywords: Silybin; Silymarin; ischemické přivykání; Preconditioning; ochranné látky; Protective Agents; Ischemia; Quercetin; Animals; Ischemic Preconditioning, Myocardial; lidé; Signalling pathways; Humans; zvířata; silymarin